Alternative Monetary Systems in the Context of Managing the National Economy - Vartsaba Vira I.; Mostipaka Olena V. (Problemi Ekonomiki, 2017)
The aim of the article is to investigate alternative monetary systems, each of which can be an algorithm for managing the national economy. By analyzing, systematizing and summarizing the scientific works of both foreign and domestic scientists, it is established that money is a phenomenon capable of managing the socio-economic relations in the time and space development coordinates following the institutionalized functioning algorithms. There justified the informational nature of money, i.e., that money is artificial information, a peculiar way of understanding social and economic relations, since the monetary subsystem is algorithmizing social and economic relations and is a derivative of the functioning and development of the national economy. The effectiveness of the national currency depends on the built-in algorithms of its functioning, which are realized in the model of the national economy. The study reflects the basic variations of potential alternative monetary systems. In particular, world money, the issuers of which are highly developed countries; S. Gesell’s “free money”; S. Sharapov’s “absolute money”; money secured by commodity values; private money; virtual money — electronic money and crypto currency, etc. Given that the socio-economic system of Ukraine as a synergetic system have been in a state of bifurcation for a long time, the article considers and proposes the most effective way of the development and functioning of the monetary system in the context of a harmonious interrelations with the national economy in time and space coordinates by direct emission of money for innovative projects of development of the national economy. Prospects for further research are the trans-scientific paradigm of managing the national economy.